The illusion of intergenerational preference aggregation: Limits of individualistic population ethics - Martin Kolmar; Klaus Stolte (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
In this paper we analyse the possibility to construct intergenerational criteria of choice within the framework of methodological individualism. The main result of this analysis is, that intergenerational criteria as an aggregation of preferences of current and future individuals do not exist. The extension of social choice theory to intergenerational problems necessarily leads to criteria that are intragenerational in nature. This fact is due to the epistemological difference between actual and potential individuals. The consequences for the structure of welfare functional in presence of intergenerational choice are analysed.
Keywords: 330; Soziale Wohlfahrtsfunktion; Generationengerechtigkeit; Methodologischer Individualismus; Theorie